3(b-4)=5-2

Simple and best practice solution for 3(b-4)=5-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(b-4)=5-2 equation:


Simplifying
3(b + -4) = 5 + -2

Reorder the terms:
3(-4 + b) = 5 + -2
(-4 * 3 + b * 3) = 5 + -2
(-12 + 3b) = 5 + -2

Combine like terms: 5 + -2 = 3
-12 + 3b = 3

Solving
-12 + 3b = 3

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + 3b = 3 + 12

Combine like terms: -12 + 12 = 0
0 + 3b = 3 + 12
3b = 3 + 12

Combine like terms: 3 + 12 = 15
3b = 15

Divide each side by '3'.
b = 5

Simplifying
b = 5

See similar equations:

| 879=629+25x | | -4d=8 | | x^3-6x^2+6x=36 | | 4f=6+23 | | -2y=2y-8 | | xy^2-5xy=0 | | 12(3+y)=5(-2y+8) | | 1x=-8 | | 9x+11x=127 | | 8(d+7)-6d= | | 2[2+(y-1)]=22 | | 7-3x+4+8x=9x-4x+x-3 | | (28b-2)-9(3b+2)=-2 | | 18x^2-14x=0 | | 4(x-1)-2x=x+7 | | 5xy(8x+y)= | | 9y=4y^2+2 | | 8+3x-7=-x+29 | | 5-(4+3x)+x=5 | | 4y+3(2y-4)=y+6 | | 11ab(4a-3b)= | | 9x+5=8+-7 | | 5-3x-(-4x+6)=8x+13 | | 676=22x+x^2 | | (5+3x)-4x= | | 2x-2(x+1)=-2 | | 1x-4x-7=5x-1x+21 | | 10x+7=-x+29 | | 2-5(z+1)=3z+1 | | y=12.5x+40 | | 2x-3(x+1)=-2 | | 7x+13=9x-9 |

Equations solver categories